SAT0201 Abatacept but not tnf inhibitors block autoantibody-mediated cytokine production by monocytes. (15th June 2017) - Bozec, A; Luo, Y; Engdahl, C; Figueiredo, C; Bang, H; Schett, G
Abstract : Background: The anti-inflammatory effect of abatacept (CTLA4-Ig) is most pronounced in patients with high-titer autoantibodies (including anti-citrullinated protein antibodies, ACPA, and rheumatoid factor, RF) even exceeding the effect of TNF inhibitors (TNFi) 1 . Considering that autoantibodies trigger inflammatory cytokine production by monocytes 2 and that abatacept bind to monocytes influencing their functional state 3 we hypothesized that abatacept, in contrast to TNFi, may effectively inhibit the production of several different cytokines by ACPA-or RF-challenged monocytes. Objectives: (i) To test whether abatacept inhibits the production of TNFa, IL-1b, IL-6 and IL-8 by monocytes exposed to ACPA or RF, (ii) to compare these effects of abatacept with those of TNFi and (iii) to investigate whether the effect of abatacept on cytokine production is based on IDO induction in monocytes. Methods: CD68+ monocytes were isolated from peripheral blood and stimulated with MCSF for 24 hours before exposing them to random IgG alone (negative control), 10mg/mL purified anti-citrullinated vimentin antibodies (ACPA), 10mg/mL RF or LPS (positive control) in cell culture plates coated with citrullinated vimentin (to allow ACPA immune complex formation). ACPA and RF stimulation was done in the presence or absence of abatacept or TNF-antibody (adalimumab) with or without IDO inhibitor 1-MT. Supernatants were analyzed for four key pro-inflammatory cytokines TNFa, IL-1b, IL-6 and IL-8 by cytokine array (R&D Proteome Profiler) after 24h. Results: Exposure to ACPA or RF dramatically induced the production of TNFa (20 fold and 27-fold, respectively) IL-1b (each 4-fold), IL-6 (12-fold and 11-fold, respectively) IL-8 (43-fold and 30-fold, respectively) in human monocytes. Abatacept significantly inhibited this up-regulation of inflammatory cytokine production with TNFa reduced by 79%, IL-1b by 74%, IL-6 by 88% and IL-8 by 83%. In contrast, TNFi did not influence autoantibody-induced production of IL-1b, IL-6 and IL-8. Inhibition of IDO by 1-MT reversed the effect of abatacept and unlocked cytokine production in the presence of ACPA and RF. Conclusions: These data show that abatacept interferes with autoantibody mediated cytokine production by induction of IDO. The fact that several different effector cytokines are inhibited simultaneously may explain the strong anti-inflammatory effect of abatacept in RA patients with high-titer ACPA and RF. References: Sokolove J, et al. Impact of baseline anti-cyclic citrullinated peptide-2 antibody concentration on efficacy outcomes following treatment with subcutaneous abatacept or adalimumab: 2-year results from the AMPLE trial. Ann Rheum Dis. 2016;75:709–14. Clavel C, et al Among human macrophages polarised to different phenotypes, the M-CSF-oriented cells present the highest pro-inflammatory response to the rheumatoid arthritis-specific immune complexes containing ACPA. Ann Rheum Dis. 2016;75:2184–2191. Bozec A, et al. T cell costimulation molecules CD80/86 inhibit osteoclast differentiation by inducing the IDO/tryptophan pathway. Sci Transl Med. 2014;6:235ra60. Acknowledgements: This project was supported by an unrestricted research grant from BMS and the IMI project BTCure. Disclosure of Interest: None declared